AKTUALISASI NILAI-NILAI IMAN DAN TAQWA DALAM IBADAH HAJI - Muhammad Ishaq, Muhith (STAI DI AL-HIKMAH, 2025)
The general hajj has been proven to be able to significantly change a person into a better person in carrying out religious teachings. Since becoming a prospective hajj, he has begun to become a figure who diligently prays in congregation to the mosque, a more islmai appearance, a more polite speech, discipline with rules, staying away from prohibitions, being more generous, and helping each other in kindness, all are great energy to improve the quality of personal, family and community. There are so many messages of kindness that can be learned by those who have fulfilled this fifth pillar of Islam.worship, and changing behavior in accordance with Islamic values.